AGR296 collaborative teaching event highlights on herbal manufacturing industries - Mohamed, Bebe Norlita; Wondi, Mohd Hafizz (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The two-hour programme commenced with an insightful sharing session by Ir. Muhamad Amirullah, a dedicated and skilled Chemical Engineer with more than nine years of progressive experience in process engineering, workplace safety, and regulatory compliance inspections. The session focused on the Chemical Management System for Herbal Manufacturing Industries, aligning with the students’ syllabus and providing essential foundational knowledge. He shared valuable insights on compliance with Good Manufacturing Practices (GMP), including maintaining comprehensive documentation, adhering to facility standards, and enforcing rigorous quality control procedures. The session also emphasised the importance of proper chemical storage and labelling, the integration of automated inventory tracking systems, and the incorporation of risk management strategies to enhance safety and efficiency throughout the production process.